The pathfinder, or, The inland sea - Cooper, James Fenimore, 1789-1851 (Cooper, James Fenimore, 1789-1851. Works. 1980., 1981)
In the sequel to The Last of the Mohicans, Natty Bumppo tries to help a small outpost on Lake Ontario.